2011
DOI: 10.4049/jimmunol.1003853
|View full text |Cite
|
Sign up to set email alerts
|

Role for E-Cadherin as an Inhibitory Receptor on Epidermal γδ T Cells

Abstract: E-cadherin is a homophilic adhesion molecule that maintains homotypic intercellular adhesion between epithelial cells such as epidermal keratinocytes. E-cadherin is also expressed on resident murine epidermal γδ T cells, known as dendritic epidermal T cells (DETCs), but they express another receptor for E-cadherin, αE(CD103)β7 integrin, as well. In this study, we analyzed functional differences between E-cadherin–mediated homophilic binding and heterophilic binding of αEβ7 integrin to E-cadherin in heterotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…On the contrary, expression of E-cadherin on lymphocytes has been analyzed in only a few studies. E-cadherin has been found on fetal thymocytes, IEL, and dendritic epidermal T cells (DETC) in the skin (21)(22)(23), and it has also recently been postulated to function as an inhibitory receptor on DETC (24). Interestingly, leukocytes infiltrating SMG of autoimmunityprone NOD mice have further been reported to express E-cadherin (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, expression of E-cadherin on lymphocytes has been analyzed in only a few studies. E-cadherin has been found on fetal thymocytes, IEL, and dendritic epidermal T cells (DETC) in the skin (21)(22)(23), and it has also recently been postulated to function as an inhibitory receptor on DETC (24). Interestingly, leukocytes infiltrating SMG of autoimmunityprone NOD mice have further been reported to express E-cadherin (20).…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is a well-known homotypic cell-cell adhesion molecule for epithelial cells, and heterotypic binding of E-cadherin on epithelial tissues to CD103 on lymphocytes is well documented (17-19). In contrast, the functional role of E-cadherin on the surface of lymphocytes has not yet been addressed in vivo (20)(21)(22)(23)(24).Examining the tissue distribution of virus-specific memory CD8 T cells after systemic lymphocytic choriomeningitis virus (LCMV) infection, we detected an enrichment of LCMV-specific memory T cells in SMG that resembled T RM cells. In the present report, we characterize the unique phenotype and the functional features of these T cells.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…22 The in vivo relevance of these findings is illustrated by CD103-deficient mice, which have reduced numbers of resident IELs and DETCs, 23 probably because of a combination of mechanisms: (1) diminished retention in epithelia; (2) an altered motility 24 ; and (3) a lack of ␣ E (CD103)␤ 7 -mediated costimulation. 25 Along the same line, retention of regulatory T cells in cutaneous wounds is mediated by CD103, 26 and TGF-␤-mediated expression of CD103 on CD8 ϩ T cells promotes their cytotoxic activity against E-cadherin ϩ targets. 27,28 Finally, CD103 expression distinguishes subpopulations of DCs that are found in lymphoid and various nonlymphoid organs and that display distinctive functions, such as cross-presentation of antigens in the draining lymph nodes (LNs), instruction of tissue-homing capacities on the activated T cells, and induction of regulatory T cells.…”
Section: E-cadherin Binds ␣ E (Cd103)␤ 7 Integrinmentioning
confidence: 99%
“…It has been found that the expression of junctional adhesion molecule-like protein 68 and high-mobility group box 1 69 by cd-T cells provides positive signals for the activation of cd-T cells, whereas stimulation with E-cadherin downregulates their functions. 70 The natural killer (NK) cell receptor family is another important group of costimulators for regulating the activity of cd-T cells, and the balance among stimulatory and inhibitory natural killer WW (NK) cell receptor signals might determine the functions of cd-T cells. For example, NKG2D and NKG2C promote the activation of cd-T cells, whereas NKG2A transfers inhibitory signals to them.…”
Section: Host Cell-derived Signalsmentioning
confidence: 99%